Improved extraction of PCR-quality community DNA from digesta and fecal samples - Zhongtang Yu; Mark Morrison (BioTechniques)
Several DNA extraction methods have been reported for use with digesta or fecal samples, but problems are often encountered in terms of relatively low DNA yields and/or recovering DNA free of inhibitory substances. Here we report a modified method to extract PCR-quality microbial community DNA from these types of samples, which employs bead beating in the presence of high concentrations of sodium dodecyl sulfate (SDS), salt, and EDTA, and with subsequent DNA purification by QIA® columns [referred to as repeated bead beating plus column (RBB+C) method]. The RBB+C method resulted in a 1.5- to 6-fold increase in DNA yield when compared to three other widely used methods. The community DNA prepared with the RBB+C method was also free of inhibitory substances and resulted in improved denaturing gradient gel electrophoresis (DGGE) profiles, which is indicative of a more complete lysis and representation of microbial diversity present in such samples.